Epsilon-negative behavior and its capacitance enhancement effect on trilayer-structured polyimide–silica/multiwalled carbon nanotubes/polyimide–polyimide composites. Issue 11 (28th February 2022) - He, Qifa; Sun, Kai; Wang, Zongxiang; Wang, Zhongyang; Yang, Pengtao; Tian, Jiahong; Duan, Wenxin; Fan, Runhua
Abstract : Silica nanoparticles are introduced into multiwalled carbon nanotube/polyimide composites to realize a weakly negative permittivity, and then a sandwich-structured composite was constructed to explore the capacitance enhancement effect. Abstract : Epsilon-negative materials show fascinating prospects in electronic components, such as coil-free inductors, stacked capacitors, and resonators, while an extremely high negative permittivity at radio-frequency blocks their further applications in electronic devices. In order to realize a weakly negative permittivity and explore its applications in the field of capacitance enhancement, we introduce silica (SiO2 ) into multiwalled carbon nanotubes and polyimide (MWCNTs/PI) composites to acquire a negative permittivity layer (SiO2 /MWCNTs/PI) and design a trilayer structure (PI–SiO2 /MWCNTs/PI–PI) consisting of a negative permittivity layer sandwiched between two positive permittivity PI layers. It is demonstrated that the permittivity of MWCNTs/PI composites transforms from positive to negative at a MWCNT content of 4.0 wt% owing to low-frequency plasma oscillation. Meanwhile, the middle-layer SiO2 /MWCNTs/PI composites show a relatively weak permittivity of −8.2@1 MHz at a low addition (only 2.5 wt%) of SiO2 and the MWCNT content is 4.0 wt%, in comparison with the conductor–polymer dielectric composites deprived of introducing SiO2 fillers. In addition, a capacitance enhancement effect (5-fold higher than PI) and a concurrently low loss tangent of ∼0.018@10 kHz are observed in sandwich composites, which benefit from epsilon-negative materials being connected to epsilon-positive materials in series. The sandwich-structured composites containing an epsilon-negative middle layer in this work provide a promising method for the design of huge-capacity capacitors.